SOME COMPLEXES OF Ni(II) CONTAINING MIXES LIGANDS (Sciences & Technology. A, exactes sciences, 2004)
Nickel (II) Complexes containing mixed ligands : semicarbazone (benzaldehyde semicarbazone-BSCH; 2-fluorobenzaldehyde semicarbazone-FSCH) and substituted pyridine {2-aminopyridine (p1) ; 4-aminopyridine (p2) ; 2,3-dicarboxypyridine (p3) ; 2-amino-3-hydroxypyridine (p4) ; 2-amino-4-methyl-pyridine (p5) and 3,4-dicarboxypyridine (p6) have been prepared. The resulted complexes have been characterized by elemental analysis, molar conductance values, magnetic moment, infrared and electronic spectral data. Complexes of the type [Ni2(SCH)2(P)4(NO3)2](NO3)2 and [Ni2(SCH)2(P)4(NO3)3]NO3 (where SCH= BSCH or FSCH, P= substituted pyridine ligands) have been proposed.